Risk Factor Analysis of Leptospirosis Incidence in Endemic Areas - Nurfitri, Nurfitri; Sukesi, Tri Wahyuni; Mulasari, Surahma Asti (Advances in Healthcare Research, 2025)
Purpose: Leptospirosis is a zoonotic disease transmitted by rats, which serve as the primary vector, and is caused by the bacterium Leptospira. This disease is a serious concern in tropical regions, including Indonesia, due to its high incidence and mortality rates. This study aims to analyze various risk factors that influence the incidence of leptospirosis in endemic areas, based on the latest scientific literature. Research Method: This study employed a systematic literature review method, searching articles published between 2020 and 2024 on the Google Scholar and PubMed platforms. From the 268 articles identified using the keywords “Leptospirosis, Rats, Risk Factors,” a selection was made based on inclusion and exclusion criteria, resulting in 10 relevant articles. Five of these articles were selected for further analysis. Results and Discussion: The results of the study indicate that several significant risk factors for leptospirosis include: the presence of Leptospira bacteria in the environment, distance of homes from waterways, standing water, garbage conditions, presence of rats, pet ownership, risky activities, use of personal protective equipment, and history of flooding. Implications: This study contributes to the formulation of risk-based prevention policies and supports more targeted public health interventions in areas endemic to leptospirosis.